2013
DOI: 10.1016/j.bone.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Epiphyseal abnormalities, trabecular bone loss and articular chondrocyte hypertrophy develop in the long bones of postnatal Ext1-deficient mice

Abstract: Long bones are integral components of the limb skeleton. Recent studies have indicated that embryonic long bone development is altered by mutations in Ext genes and consequent heparan sulfate (HS) deficiency, possibly due to changes in activity and distribution of HS-binding/growth plate-associated signaling proteins. Here we asked whether Ext function is continuously required after birth to sustain growth plate function and long bone growth and organization. Compound transgenic Ext1f/f;Col2CreERT mice were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
5
32
0
Order By: Relevance
“…It has remained unclear and controversial as to whether and how the HS deficiency causes exostosis formation, why the exostoses form near but not inside the growth plates, whether the exostoses are formed by aberrant function of growth plate chondrocytes themselves or involve perichondrial progenitors, and what growth factors trigger and sustain exostosis outgrowth ( 4,53 ). In studies we and others carried out previously, we found that mutant mice lacking one allele of Ext1 or Ext2 did not reproduce the human HME skeletal phenotype, while double heterozygous Ext1 +/− ; Ext2 +/− mice or conditionally ablated Ext1 −/− mice did ( 55, 56 ). The data strongly indicated that a partial decrease in HS levels such as that elicited by a simple heterozygous EXT mutation is insufficient for exostosis formation and HME progression, but a deeper decrease is required.…”
Section: Hs- and Hspg-associated Pathologiesmentioning
confidence: 67%
“…It has remained unclear and controversial as to whether and how the HS deficiency causes exostosis formation, why the exostoses form near but not inside the growth plates, whether the exostoses are formed by aberrant function of growth plate chondrocytes themselves or involve perichondrial progenitors, and what growth factors trigger and sustain exostosis outgrowth ( 4,53 ). In studies we and others carried out previously, we found that mutant mice lacking one allele of Ext1 or Ext2 did not reproduce the human HME skeletal phenotype, while double heterozygous Ext1 +/− ; Ext2 +/− mice or conditionally ablated Ext1 −/− mice did ( 55, 56 ). The data strongly indicated that a partial decrease in HS levels such as that elicited by a simple heterozygous EXT mutation is insufficient for exostosis formation and HME progression, but a deeper decrease is required.…”
Section: Hs- and Hspg-associated Pathologiesmentioning
confidence: 67%
“…The penetrance of the phenotypes is largely comparable between the two models, except for the higher occurrence of osteochondromas in the distal humerus, proximal radius, and distal femur and the lack of scoliosis in the Fsp1-Ext1 CKO model. Additionally, unlike Col2a1-Ext1 CKO mice, which exhibit enhanced osteoclastogenesis (26), there was no increase in the number of osteoclasts in Fsp1-Ext1 CKO mice (Supplemental Figure 3). Overall, these results demonstrate that loss of Ext1 restricted to perichondrial progenitor cells is sufficient to induce MHE-like osteochondromagenesis in various bones.…”
Section: Aberrant Differentiation Of Perichondrial Cells In Col2a1-ext1mentioning
confidence: 98%
“…Meanwhile, it remains to be determined whether the latter phenotype is secondary to osteopenia or a primary developmental defect independent of osteopenia, as abnormalities in secondary ossification centers are not a common feature seen in a number of severely osteopenic mouse lines. Interestingly, a chondrocyte-targeted Ext1 knockout induced by a Col2-based Cre driver causes a delay in secondary ossification center formation (46), suggesting that HS may be functionally involved in the development of a secondary ossification center. This chondrocyte-targeted knockout mouse model also exhibits a reduction in trabecular bone volume (46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a chondrocyte-targeted Ext1 knockout induced by a Col2-based Cre driver causes a delay in secondary ossification center formation (46), suggesting that HS may be functionally involved in the development of a secondary ossification center. This chondrocyte-targeted knockout mouse model also exhibits a reduction in trabecular bone volume (46). Considering that the Col2-Cre transgene exhibits a leaky expression in osteochondroprogenitors (47), this phenotype may be due to Ext1 ablation in the osteoblastic lineage.…”
Section: Discussionmentioning
confidence: 99%